Lipid metabolism during exercise - Klein, S. (1996)
Ingestion of typical dietary fat is not a useful approach for providing fuel during exercise because it may take several hours for the long-chain fatty acids to be oxidized. Long-chain triglycerides are emptied slowly from the stomach, packaged into chylomicrons in the small intestine, and secreted into the lymphatic system before entering the bloodstream. Only a portion of triglycerides present in circulating chylomicrons ultimately provide fatty acids to muscle. In contrast, medium chain triglycerides (MCTs) have been proposed as a potential ergogenic fuel during exercise and are currently present in several commercially prepared sport bars. Medium-chain triglycerides are emptied rapidly from the stomach,11 rapidly absorbed and hydrolyzed by the small intestine, and secreted directly into the systemic circulation. Furthermore, medium-chain fatty acids do not require the acylcarnitine transferase system to cross the inner mitochondrial membrane in liver and muscle for oxidation. However, several studies have demonstrated that oral supplementation with MCTs is unlikely to improve performance during endurance exercise. The amount of MCTs that can be given orally is limited to approximately 25-30 grams because diarrhea and other gastrointestinal side effects are common with higher doses. Furthermore, although orally administered medium-chain triglycerides are readily oxidized, they do not spare muscle glycogen during either moderate or high-intensity exercise.